Tunable optical parametric generator based on the pump spatial walk-off - Cavanna, Andrea; Just, Felix; Sharapova, Polina; Taheri, Michael; Leuchs, Gerd; Chekhova, Maria V. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Förderung inklusiven Lernens im naturwissenschaftlich-technischen Sachunterricht der Grundschule. Vortrag auf der 4. Jahrestagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Blumberg, Eva; Fromme, Theresa; Hellmich, Frank

Zur Feinstaubabscheidung aus Holzfeuerungsanlagen mit precoatierten Oberflächenfiltern - Schiller, Sascha

Tailoring the textural properties of hierarchical porous carbons using deep eutectic solvents - Lopez Salas, Nieves; Carriazo, D.; Gutiérrez, M. C.; Ferrer, M. L.; Ania, C. O.; Rubio, F.; Tamayo, A.; Fierro, J. L. G.; del Monte, F. (Journal of Materials Chemistry A)
DESs containing resorcinol, urea and choline chloride allow the preparation of monolithic carbons with bicontinuous porous structures, the pore dimension of which can be easily tailored by the molar ratio of the components at the original DES.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Kinder mit Lernschwierigkeiten in der Grundschule - Miller, Susanne; Kottmann, Brigitte (Differenz - Ungleichheit - Erziehungswissenschaft)

"Und dann war das auch noch so ein kleines, zartes Persönchen": Grundschullehrkräfte im Entscheidungsdilemma zwischen Fördern und Selektieren - Miller, Susanne; Kottmann, Brigitte (Diagnostik im Kontext inklusive Bildung)

Selektion inklusive?! Widersprüche bei der umsetzung von Inklusion in der Schule - Kottmann, Brigitte; Miller, Susanne (Empirische Forschung im Kontext Schule)

Quantum technology: from research to application - Schleich, Wolfgang P.; Ranade, Kedar S.; Anton, Christian; Arndt, Markus; Aspelmeyer, Markus; Bayer, Manfred; Berg, Gunnar; Calarco, Tommaso; Fuchs, Harald; Giacobino, Elisabeth; Grassl, Markus; Hänggi, Peter; et al. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

In-lab ALOHA mid-infrared up-conversion interferometer with high fringe contrast @λ = 3.39 μm - Szemendera, L.; Darré, P.; Baudoin, R.; Grossard, L.; Delage, L.; Herrmann, Harald; Silberhorn, Christine; Reynaud, F. (Monthly Notices of the Royal Astronomical Society)
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Local Sampling of the Wigner Function at Telecom Wavelength with Loss-Tolerant Detection of Photon Statistics - Harder, G.; Silberhorn, Christine; Rehacek, J.; Hradil, Z.; Motka, L.; Stoklasa, B.; Sánchez-Soto, L. L. (Physical Review Letters)
Keywords: General Physics and Astronomy